Moderasi Beragama di Tengah Masyarakat Plural (Studi Kasus Pada Masyarakat Desa Wonorejo Kecamatan Banyuputih Kabupaten Situbondo) - Imam Safi'i; M. Alfin Fatikh; Mohamad Toha; Fatkhiyatus Su'adah (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Wonorejo Village's society in Banyuputih Situbondo Regency has four religions that live harmoniously. Islam is a majority group, while other religions are a minority group. In religious and state life, there are guidelines for life that can become a medium of harmony among them, namely socio-community ethics. In this paper, two objectives must be answered, including a) Knowing how the dynamics of the lives of the people of Wonorejo Village and B) knowing how the attitude of religious moderation is built in the plural society that occurs in the Wonorejo village as the capital of national and dynamic national life. To answer the purpose of this study, the author uses a type of qualitative research using the social construction theory of Peter L. Berger and Tomas Luckman. The results of this study show that the dynamics of the lives of the people of Wonorejo Village are classified as harmonious, peaceful, and tolerant. Furthermore, the attitude of religious moderation in this village takes time to happen. Three forces construct the lives of the people of Wonorejo Village until the attitude of religious moderation during plural society is pitched. Among them are the understanding and awareness of the individual, the existence of culture and tradition, and the role of agents. These three moments run simultaneously and are dialectic three moments, namely the moment of externalization, objectivation, and internalization.